Crowdsourcing financial information to change spending behavior - Francesco D'Acunto; Alberto G. Rossi; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2019)
We document five effects of providing individuals with crowdsourced spending information about their peers (individuals with similar characteristics) through a FinTech app. First, users who spend more than their peers reduce their spending significantly, whereas users who spend less keep constant or increase their spending. Second, users' distance from their peers' spend-ing affects the reaction monotonically in both directions. Third, users' reaction is asymmetric - spending cuts are three times as large as increases. Fourth, lower-income users react more than others. Fifth, discretionary spending drives the reaction in both directions and especially cash withdrawals, which are commonly used for incidental expenses and anonymous transactions. We argue Bayesian updating, peer pressure, or the fact that bad news looms more than (equally-sized) good news cannot alone explain all these facts.
Keywords: D12; D14; D91; E22; G41; 330; FinTech; learning; beliefs and expectations; peer pressure; financial decision-making; saving; consumer finance